Ohabei Shalom Synagogue at 11 Union Park Street, ca. 1890 - Boston Globe (Tufts Archival Research Center, 2005)
Street-level view south-southwest of the Ohabei Shalom Synagogue at 11 Union Park Street, located between Shawmut Avenue to the northwest and Washington Street to the southeast. The facade of the synagogue faces northeast towards Union Park Street. 8 1/2 x 6, 8 1/2 x 6 7/16 overall Photographs